Iterative learning control of an Euler-Bernoulli beam with time-varying boundary disturbance - Wang, Yingying; Wu, Wei; Lou, Xuyang; Görges, Daniel (Computers & mathematics with applications (1987), 2024)
This paper investigates the stabilization of Euler-Bernoulli beam systems modeled by a partial differential equation (PDE) with unknown time-varying disturbance. An iterative learning controller is designed using only boundary state feedback to realize the vibration control subject to unknown boundary disturbance. The well-posedness for the closed-loop system is given by the operator semigroup theory. Furthermore, the exponentially stable for the closed-loop system is proved by the Lyapunov method. The comparisons with existing results are made to demonstrate the effectiveness and advantages of the proposed boundary iterative learning control method.